Roles of agricultural biotechnology in ensuring adequate food security in developing societies - Okonkwo Onyebuchi Kingsley (Global Journal of Plant and Soil Sciences, 2017)
Agriculture is asked to satisfy two apparently contradictory needs; to become more productive and at the same time more sustainable, that is, to supply the food needed without depleting renewable resources. While agricultural biotechnology holds enormous promise for significantly increasing food production and relieving already strained land and water resources in most developing societies, it has become an emotional issue creating the strongest sense of unease and resistance among some consumers, developing countries farmers, environmental groups and some societies. This review appraises the food and fibre situations in developing societies so as to understand the roles which agricultural biotechnology could play therein. It revealed that the outlook for developing societies in food and fibre production is particularly grim; however, increases in crop and animal yields and therefore the availability of food to feed the ever growing population of developing societies can be achieved through the adoption of biotechnology practices. The paper concludes with the recommen-dation that individual countries need to identify their specific national priorities and preferences in food production, and harness the growing body of science and innovations in genetic engineering to address specific issues.